Analysis of Sanitation Conditions and Hygiene Behavior in the Raudhatul Athfal Environment, Sleman Regency: A Survey Study - Fahrunnisa, Fahrunnisa (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze sanitation conditions and hygienic behaviors in Raudhatul Athfal (RA) schools in Sleman Regency, Indonesia, to highlight the important role of these factors in supporting children's health and preventing the spread of disease. The relevance of this study is underscored by alarming statistics from the World Health Organization (2020), which show that poor sanitation contributes significantly to preventable childhood diseases. This study used a survey method, data were collected from 15 RA schools through direct observation of sanitation facilities and semi-structured interviews with principals and staff. Descriptive statistical analysis was used to interpret the data and visualize the findings. The findings revealed that while 86.67% of schools reported good water quality and 93.33% kept toilets clean, only 33.33% provided separate toilets for boys and girls. In addition, 66.67% of schools offered child-friendly toilet facilities. In terms of hygiene behavior, 93.33% of schools promoted handwashing education during critical times, but only 73.33% involved students in waste sorting and recycling practices. The study concluded that, although sanitation practices were positive in most RA schools, there were areas for improvement, particularly in gender-sensitive sanitation and waste management. Improving education on waste sorting could further enhance environmental sustainability. This study provides valuable insights for policymakers and educators to strengthen sanitation policies and practices in early childhood education settings. Future studies should investigate the long-term impact of improved sanitation and hygiene education on students’ health and academic performance.